Prevalence of hypercementosis and frequency of possible etiological factors in a Turkish subpopulation - Defne, Yalcin Yeler; Ilknur, Eninanc; Melike, Koraltan; Simeyya, Baybars; Fatmanur, Ketenci; Yener, Unal (Wolters Kluwer Medknow Publications, 2021)
Objective: The aim of this study was to investigate the prevalence and types of hypercementosis and the frequency of possible etiological factors in a large sample of Turkish central Anatolian population. Subjects and Methods: A cross-sectional study was performed using panoramic radiographs of 1176 randomly selected adult patients with an age range of 18-96 years, who presented to the Department of Oral and Maxillofacial Radiology of the Faculty of Dentistry, Cumhuriyet University (Sivas, Turkey) for dental care. Patients were questioned about the presence of systemic diseases. Panoramic radiographs of the patients were examined for the presence and types of hypercementosis (diffuse, focal and shirt sleeve cuff) and the frequency of local factors that may be associated with hypercementosis. Chi-square and t-tests were used for statistical analysis. Results: Hypercementosis was detected in 128 of 1176 patients. In total, 85.6% of the teeth with hypercementosis had a diffuse, 7.5% had a focal, and 6.8% had a shirt sleeve cuff type. Hypercementosis was observed most frequently in the mandibular (P < 0.05) and the premolar region. Gender-related differences were nonsignificant (P > 0.05). Atherosclerosis, osteoporosis, and multiple diseases were reported more frequently in individuals with hypercementosed teeth (P < 0.05). While idiopathic origin (39.3%), bruxism (30%), and inflammation (24.37%) were the most prevalent local etiological factors, impacted teeth (1.25%) and history of trauma (0.62%) were less common. Conclusion: The prevalence of hypercementosis was 10.8% in the study population. The lesions were more common in the mandibule. Idiopathic origin was the most common factor associated with hypercementosis.
Keywords: Etiology; hypercementosis; prevalence; systemic disease; Turkish population